الفهم الصحيح في الدعوة الإسلامية: اعتدال النبي ﷺ وأصحابه أنموذجا: The research on "The Correct Understanding of Islamic Dawah: The Moderation of the Prophet ﷺ and His Companions as a Model" (Khairulummah, 2024)
The research on "The Correct Understanding of Islamic Dawah: The Moderation of the Prophet ﷺ and His Companions as a Model" highlights the balanced and moderate approach that the Prophet Muhammad ﷺ and his companions applied in spreading the message of Islam. The essence of the research is to emphasize the importance of moderation in Islamic dawah, avoiding extremes, and adopting a comprehensive approach to teaching and inviting people to Islam.Key points in the research include:• Prophet Muhammad's Moderation: The Prophet ﷺ was a model of balance, emphasizing both the spiritual and practical aspects of Islam. His dawah was not forceful or rigid but was based on wisdom, patience, and understanding.• Example of the Companions: The companions of the Prophet ﷺ followed his example by spreading Islam with wisdom and moderation, considering the needs of different people and contexts.• Avoidance of Extremism: Both the Prophet ﷺ and his companions avoided any form of extremism, whether in belief or action, and ensured that the message of Islam remained accessible to all.• Balanced Methodology: The research also underscores the balanced methodology of dawah—encouraging dialogue, understanding, and the use of gentle persuasion rather than coercion.In conclusion, the study advocates for the adoption of the Prophet ﷺ and his companions' approach as a model for contemporary Islamic dawah, emphasizing moderation, wisdom, and the avoidance of extremism in all aspects of inviting others to Islam.